2020
DOI: 10.3390/ijerph17082692
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Perception and Influencing Factors in Chinese Patients with Heart Failure: A Preliminary Exploration

Abstract: A growing body of evidence supports the fact that optimal health-related quality of life is largely dependent on patient competence in symptom perception. However, many studies have reported poor symptom perception in patients with heart failure. In China, there has been no previous research on assessing the symptom perception ability of patients with heart failure. This study aimed to describe how Chinese patients with heart failure perceive their symptoms, as well as to explore their influencing factors. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
0
16
1
Order By: Relevance
“…Higher scores mean that patients perceived a higher symptom burden. The Chinese version of the HFSPS had acceptable validity and reliability in patients with HF, with a Cronbach's α of 0.690 (Luo et al, 2020). The Cronbach's α of the HFSPS was 0.634 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores mean that patients perceived a higher symptom burden. The Chinese version of the HFSPS had acceptable validity and reliability in patients with HF, with a Cronbach's α of 0.690 (Luo et al, 2020). The Cronbach's α of the HFSPS was 0.634 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…8 Moreover, Dodd's theory among cancer sufferers argued that patients waited to perform self-care until adverse effects were severe or persistent. 15 Hence, severe NYHA classification indicated severe heart dysfunction and more symptoms, 6 which promoted patients to practice self-care recommendations. mediated by self-care confidence.…”
Section: Problem-related Factors Of Self-care In Chronic Heart Failurementioning
confidence: 99%
“…Other investigators have reported depression to be a predictor of clinical events 50 or associated with physical HF symptoms. 51,52 Our findings may differ based on similar depression scores between those with and without a clinical event. The situational factor of being in a relationship also influenced clinical events.…”
Section: Predictors Of Readmissionmentioning
confidence: 71%